Student and Teacher Evaluations about Design Based Science Education: “Heat Insulation is a Gain for Country” Activity - Esra Bozkurt Altan; Engin Karahan (Elementary Education Online, 2023)
This study aimed to investigate students’ evaluations about “Heat Insulation is a Gain for Country” activity designed based on Design Based Science Education (DBSE) and the instructor’s views about her experiences during the activity. The participants of this single case study are 32 students and 1 teacher. The evaluations of the students were collected via DBSE Student Evaluation Survey and focus group interviews, whereas teacher view data was collected via an unstructured interview. Descriptive (survey and individual interview) and content analysis (focus group interview) methods were used to analyze the data. The students’ statements indicated that DBSE processes prepare them for real life, raise their awareness about engineering design, and motivate them for learning. Also, DBSE based “Heat Insulation is a Gain for Country” activity can be an alternative for teachers who want to integrate STEM education in science classes.